Kajian Sistematis Literatur Tentang Pengembangan Media dan Materi IPA Interaktif di Sekolah Dasar Berbasis Keterampilan Abad 21 - Rorimpandey, Widdy H.F.; Kalengkongan, Jeane; Carolina Dien, Jini; Asari Lengkong, Afrilia; Leonita Horman, Meisara (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2025)
The development of 21st century education demands innovation in Science (IPA) learning at the elementary school level, emphasizing not only knowledge transfer but also the cultivation of critical thinking, creativity, collaboration, and communication skills. This study aims to systematically analyze the literature discussing the development of interactive science learning media and materials in elementary schools relevant to the enhancement of 21st century skills. The research employed a Systematic Literature Review (SLR) method consisting of identification, selection, analysis, and synthesis stages of scientific articles published between 2018 and 2024. Data sources were obtained from national and international databases such as Google Scholar, DOAJ, and Garuda. The findings indicate that the development of digital-based interactive media—such as Articulate Storyline, Educandy, Augmented Reality, and virtual laboratories—has a positive impact on students’ conceptual understanding, learning motivation, and scientific literacy. Furthermore, science materials designed using contextual and problem-based approaches were found to be effective in integrating 21st century skills. The main challenges identified include limited teacher competence in technology use, unequal digital infrastructure, and the lack of comprehensive evaluations based on 21st century competencies. This review recommends continuous teacher training, the development of student-centered learning media, and collaboration between educational institutions and technology developers to create innovative, adaptive, and skill-oriented science learning environments.